Physical Activity in Natural Environments Is Associated With Motivational Climate and the Prevention of Harmful Habits: Structural Equation Analysis - Castro-Sánchez, Manuel; Zurita-Ortega, Félix; Pérez-Turpin, José Antonio; Cachón-Zagalaz, Javier; Cofre-Bolados, Cristian; Suarez-Llorca, Concepción; Chacón-Cuberos, Ramón (Frontiers in Psychology, 2019)
Background: Practising physical activity in a natural environment has various benefits that make it an ideal setting to develop healthy behaviours and thereby diminish unhealthy habits. The objective of this study was to develop and verify an explicative model for motivational climate in sport, considering its potential influence on alcohol and tobacco consumption. Methods: The study included 2273 adolescents from Granada (Spain), analysing motivational climate (PMCSQ-2), alcohol consumption (AUDIT) and tobacco consumption (FTND). Multi-group structural equation modelling was conducted, yielding an excellent fit (χ2 = 168.170; gl = 32; p = 0.00; CFI = 0.972; NFI = 0.966; IFI = 0.972; RMSEA = 0.045). Results: The main findings were: a negative relationship between task climate and alcohol consumption among students practicing physical activities in a natural environment; a positive relationship between ego climate and alcohol consumption among those practicing other types of physical activity; and a positive and direct relationship between alcohol and tobacco consumption, which was stronger among those who did not practise physical activity in a natural environment. Conclusions: We conclude that physical-sport activity practised in nature is a key to acquiring healthy patterns characterised by intrinsic motivations in sport and lower consumption of harmful substances.